Peningkatan Pengetahuan dan Keterampilan Berkarya Seni Budaya Lokal Untuk Meningkatkan Wawasan Kebudayaan Nasional Pada PPG Prajabatan Seni Budaya - Jayadi, Karta; M, Rahma; Akmal, Muhammad Syafruddin; Saputra, Andi Taslim; Suyudi, Muhammad (Sureq: Jurnal Pengabdian Masyarakat Berbasis Seni dan Desain, 2025)
As aspiring educators, pre-service students in the PPG Arts and Culture Program play a pivotal role in sustaining and innovating local artistic traditions. Yet, gaps in both theoretical and practical mastery remain evident. To bridge this divide, a specialized training program was implemented to elevate the professional expertise of PPG UNM students in local artistic creation—spanning dance, theater, and two- and three-dimensional visual arts. Post-intervention assessments revealed marked advancements in participants’ conceptual grasp and technical execution across diverse local art forms. Notably, the trainees exhibited an enhanced ability to produce works deeply rooted in local aesthetics, whether through visual compositions or performative expressions in dance and theater. This initiative underscores the transformative potential of structured pedagogy in fostering culturally anchored artistic proficiency among future arts educators.